Faktor-Faktor yang Mempengaruhi Kecenderungan Kecurangan Akutansi pada Koperasi Simpan Pinjam dan Pembiayaan Syariah di Kota Padang - Aabidah Haswenova; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to examine the factors that influence the occurrence of accounting fraud tendencies. The independent variables used in this study are the appropriateness of compensation, conflict of interest, the effectiveness of internal controls, and information asymmetry while the dependent variable is the tendency of accounting fraud. The population in this study were KSPPS managers and administrators in the city of Padang with the sampling technique being purposive sampling. The data used is primary data obtained by distributing questionnaires to KSPPS administrators and managers in Padang City. Data from this questionnaire were analyzed using the IBM SPSS 23 application. The results of this study indicate that the suitability of compensation has a negative effect on the tendency of accounting fraud and information asymmetry have a positive effect on the tendency of accounting fraud, while conflict of interest and the effectiveness of internal control does not have an effect on the tendency of accounting.